Decent gig work in Sub Sahara Africa?. (February 2023) - Ayentimi, Desmond Tutu; Abadi, Hossein Ali; Burgess, John
Sub-Saharan Africa (SSA) economies are entrenched in traditional economic and employment structures driven by the informal sector. There is a small and regulated formal sector, built upon public sector employment. Unlike the discussion of gig work in advanced capitalist economies, the development of gig work in SSA is within an environment where employment standards and labour regulations are largely absent. The concern in developed countries is that gig work erodes the norm of regulated employment; in developing economies gig work is part of the norm of informal and unregulated employment. Gig work in SSA offers the potential for formalisation of production and work, new forms of agency, and supporting decent work. However, the challenge is how to realise this potential. The role of platforms in developing and transmitting decent work protocols into gig contracts is discussed as a potential means for supporting decent work in SSA.